Legal Aspects of Consumer Protection in Online Lending Services in the Era of Inclusive Digital Transformation (Open Society Conference, 2025)
This study examines the legal aspects of consumer protection in online lending services (fintech lending) in Indonesia during the era of inclusive digital transformation. Although several regulations exist, such as Financial Services Authority Regulations (POJK), the Consumer Protection Law, and the Personal Data Protection Law, legal protection for consumers still faces various normative and implementation challenges. These include the absence of a specific fintech law, weak supervision of illegal fintech operators, low consumer digital literacy, and ineffective dispute resolution mechanisms. This study recommends the establishment of a comprehensive and adaptive legal framework, including the enactment of a national fintech law, strengthening the role of regulators, developing supervision systems and digital dispute resolution mechanisms, and enhancing consumer digital financial literacy. Such improvements aim to strengthen consumer protection in fintech lending services responsively and inclusively amidst the dynamics of modern financial technology.